Ocular surface squamous neoplasia in a young adult - its nature and unusual course - Panda, A; Sasikala, NK (Nepalese Journal of Ophthalmology, 2011)
Background: We describe a case o f a recurrent ocular surface squamous neoplasia (OSSN) in a 37-year-old male with a mass at the infero-temporal quadrant along with an isolated primary lesion at the upper nasal quadrant for the last five months with a past history of surgical excision 7 years ago for a nodular mass in the same eye. The mass showed delayed response to Mitomycin C (MMC) therapy and finally developed limbal stem cell deficiency. Case report: A 37-year-old male presented with a five-month history of foreign body sensation and localized conjunctival hyperemia and two progressively enlarging bumps over the limbus in the left eye. The past history stated a surgical excision, done 7 years ago, for a nodular mass in the same eye. A clinical diagnosis of recurrent OSSN was made, and confirmed by impression cytology. The patient received initial treatment with 0.02 % MMC, but did not show any improvement even after 3 cycles, but later showed marked chemoreduction with 0.04 % MMC on two cycles and a complete resolution of the neoplasia after two more cycles. Impression cytology at six months revealed no abnormality. But at the 10-month follow-up, limbal stem cell deficiency was observed. Conclusion: While examining, managing and follow-up of a case of OSSN, one needs to know the atypical nature and response of the tumour. Long-term follow-up in these cases is mandatory. DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5297 Nepal J Ophthalmol 2011; 3(2): 199-201